Policy work and capacities in a developing country: evidence from the Philippines. Issue 1 (2nd January 2018) - Saguin, Kidjie; Ramesh, M.; Howlett, Michael
Abstract : Are policy work and the capacities required in developing countries different from those in the developed world? This article addresses this question using data from a survey of policy professionals in the Philippines. The individuals surveyed have similar characteristics as their counterparts in developed countries, but their specific policy analytical style appears to be largely coordinative rather being directed at substantive and procedural aspects of policy work – which raises questions about whether or not their capacities as various skills and resources enable them to carry out their work effectively. An important finding is that, despite their work being primarily of an analytical nature, they are more comfortable performing political and operational tasks than conducting substantive, rigorous analysis. Overall, while organisational systems and processes are in place, systemic capacities, particularly political capacity, continue to be an on-going constraint to their work.